2016
DOI: 10.1016/j.hkjot.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cognitive and Psychological Symptoms on Work Productivity and Quality of Life among Breast Cancer Survivors in Hong Kong

Abstract: Objective/BackgroundEmployed breast cancer survivors (BCS) may experience residual symptoms that can impact their work productivity and quality of life (QoL), but it is unclear whether such associations exist among BCS in Hong Kong. Therefore, this study was designed to explore the symptom burden (cognitive limitation and psychological distress) of employed BCS in HK, and to investigate whether such factors are related to work productivity and QoL.MethodsA cross-sectional study including employed BCS (n = 30),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 33 publications
(53 reference statements)
1
32
0
Order By: Relevance
“…65% = Caucasian; 45% = African American.8% = < secondary education; 41% = completed secondary education; 51% > secondary education. 84% reported employment 60% = Mastectomy 27% = Lumpectomy 73% = Chemotherapy 57% = Radiation 36% = Hormone therapy 67 women were diagnosed between 2005 and 2011, 3 were diagnosed between 1981 and 1999 Center of Epidemiologic Studies Depression Scale (CES-D) FACT-G EORTC QLQ-BR23 Depression was significantly correlated with QoL Body image, physical attractiveness, and femininity, sociodemographic and clinical variables Cheng A.S.K., 2016 [ 43 ] Cross-sectional China 90 women aged between 18 and 60 years. 30 were breast cancer survivors, 30 had musculoskeletal conditions, and 30 healthy women.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…65% = Caucasian; 45% = African American.8% = < secondary education; 41% = completed secondary education; 51% > secondary education. 84% reported employment 60% = Mastectomy 27% = Lumpectomy 73% = Chemotherapy 57% = Radiation 36% = Hormone therapy 67 women were diagnosed between 2005 and 2011, 3 were diagnosed between 1981 and 1999 Center of Epidemiologic Studies Depression Scale (CES-D) FACT-G EORTC QLQ-BR23 Depression was significantly correlated with QoL Body image, physical attractiveness, and femininity, sociodemographic and clinical variables Cheng A.S.K., 2016 [ 43 ] Cross-sectional China 90 women aged between 18 and 60 years. 30 were breast cancer survivors, 30 had musculoskeletal conditions, and 30 healthy women.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that higher scores for posttraumatic growth were associated with a higher QoL [27,54]. While higher scores on negative affect and cognitive limitations were found to be associated with a lower QoL [43,46]. Work limitations were reported to have no significant impact on QoL [43].…”
Section: Assessing the Influence Of The Psychosocial Determinants On mentioning
confidence: 99%
See 3 more Smart Citations